In‐Situ Carbon Doping of TiO2 Nanotubes Via Anodization in Graphene Oxide Quantum Dot Containing Electrolyte and Carburization to TiOxCy Nanotubes. Issue 5 (13th February 2015) - Favaro, Marco; Leonardi, Silvia; Valero‐Vidal, Carlos; Nappini, Silvia; Hanzlik, Marianne; Agnoli, Stefano; Kunze‐Liebhäuser, Julia; Granozzi, Gaetano
Abstract : Anodic production of self‐organized titania nanotubes (TNTs) in an electrolyte enriched with graphene oxide quantum dots (GOQDs) is reported. The TNT‐GOQD composites grown under these conditions show in‐situ carbon doping, leading to the formation of anatase TiO2 domains and to the reduction to substoichiometric oxide (TiO x ) and TiC. Surface science and electrochemical techniques are used in synergy to reveal that graphitic carbon is incorporated into TiO2 upon anodic nanotube growth promoting the formation of oxygen vacancies and thus TiO2 reduction. Upon annealing in ultrahigh vacuum, titanium oxycarbide (TiO x C y ) is formed at temperatures ≥400 °C, where the material changes from a semiconductor to a semimetal. At the solid/liquid interface, the apparent electron donor density increases from as‐grown TNTs to as‐grown TNT‐GOQD composites due to the carbon doping, and the conductivity increases further with annealing temperature due to the increasing concentration of coordinatively unsaturated C atoms, crystallinity, and TiO2 reduction. The materials synthesized and characterized in this study find application in different areas ranging from visible light photocatalysis and photo‐electrochemistry to use as Li‐ion battery anodes and electrocatalyst supports, because it is possible to gradually tune the density of states below the Fermi level, which can be referred to as band‐gap engineering. Abstract : The anodic production of self‐organized titania nanotubes in an electrolyte enriched with graphene oxide quantum dots is reported, while composites grown under these conditions show in‐situ carbon doping, leading to the formation of anatase domains and to the reduction to substoichiometric oxide and TiC. The materials synthesized and characterized in this study find application in different areas ranging from visible light photocatalysis and photo‐electrochemistry to the use as Li‐ion battery anodes and electrocatalyst supports.